Klasfisikasi Jenis Ikan Koi Menggunakan Ekstraksi Warna HSV dan Metode Adaptive Neuro-Fuzzy Inference System (ANFIS) - Hutagalung, Deanna Durbin; Galan Min Aqshal (Jurnal ICT: Information Communication & Technology, 2023)
Koi fish (Cyprinus Carpio) is one of the ornamental fish that is very attractive, both in color and in various types, so this fish is popular with many people as an ornamental fish and is used as a business prospect. With the increasing development of cultivation and the development of new koi fish color characteristics, this is both good news and new problems. This is due to unfamiliarity with the types of koi fish, especially for beginners and those who are still new to the introduction of koi fish. To overcome this problem, an application is needed to classify koi fish types. Using Matlab software, the Adaptive Neuro-Fuzzy Inference System (ANFIS) algorithm for classifying objects based on color, and the Hue Saturation Value (HSV) method for color feature extraction. The combination of ANFIS and HSV produces a quite high accuracy for determining the type of koi fish with a total of 189 images of data, divided into two, namely training data with a total of 150 and test data with 39. Results of evaluating the classification of Koi fish types using applications obtained from the HSV and ANFIS methods, The training data obtained a value of 100%, and the test data value was 48.71%. Abstrak- Ikan Koi (Cyprinus Carpio) merupakan salah satu ikan hias yang sangat menarik baik warna maupun jenis yang beragam sehingga ikan ini banyak digemari orang sebagai ikan hias dan dijadikan prospek bisnis. Dengan semakin berkembangnya budidaya dan pengembangan ciri warna ikan koi baru, menjadi kabar baik sekaligus masalah baru. Hal ini disebabkan karena ketidaktahuan terhadap jenis ikan koi khusunya bagi pemula dan masih baru dalam pengenalan ikan koi. Untuk mengatasi masalah tersebut, maka dibutuhkan sebuah aplikasi untuk klasfikasi jenis ikan koi. Menggunakan software Matlab, algoritma Adaptive Neuro-Fuzzy Iference System (ANFIS) untuk klasifikasi terhadap objek berdasarkan warna dan metode Hue Saturation Value (HSV) untuk ekstraksi fitur warna. Kombinasi antara ANFIS dengan HSV menghasilkan akurasi yang cukup tinggi untuk penentuan jenis ikan koi dengan total data 189 citra, dibagi dua yaitu data latih dengan jumlah 150 dan data uji 39. Hasil evaluasi klasifikasi jenis ikan Koi menggunakan aplikasi yang diperoleh dari metode HSV dan ANFIS, data latih diperoleh nilai sebesar 100%, dan nilai data uji 48,71 %.